Pendampingan Imunisasi dan Sosialisasi Campak Anak Posyandu di Desa Mekarsari - Listian Indriyani Achmad; Kisanda Midisen; Sarwo Edy; Siti Juariah; Rini Setyowati (DPPM Universitas Pelita Bangsa, 2021)
As improving health is an important part of national development. The aim is to increase the awareness, desire and ability of the community to live a healthy life. To achieve optimal health status. Thus, Posyandu is one of the resources and community involvement in the health sector. Established by the community, for the community, for the community Posyandu-style community service activities use methods that include developmental discussions and question and answer sessions, describing the opportunities that Posyandu offers and its usefulness,Benefits of sufficient markdown type recommendations for babies, distributing masks and hand sanitisers to mothers who come to Posyandu. stress activities monitored by posyandu strictly follow health protocols, distributing child universal benefit amenity booklets, changing posters where mothers and children gather. Warmly inviting people from all walks of life to visit the posyandu and giving a brief explanation of the types of immunisations and the benefits to children's health. These socialisation and mentoring activities continue to be held regularly and more intensively by involving more parties, including the media and local government. The use of social media and mass media can be an effective tool in disseminating information about child health and its shortcomings.